Pengembangan Model Sentra Industri Kreatif Motif Kerajinan Minang melalui Adaptability IKM, Inovasi, Kewirausahaan dan Keunggulan Kompetitif - Rahim, Rida; Husni, Tafdil; yanti, yanti (Jurusan Manajemen Fakultas Ekonomi Universitas Negeri Padang, 2014)
Small industries are required to improve and maintain its competitiveness in quality and diversification of products that can adapt (adaptability) with market demand and constantly innovating in producing its products so as to achieve competitive advantage (competitive advantage) both in the national market as well as International market. This study used qualitative methods. Qualititatif method begins with the implementation of research results that have been obtained in the first year, then offer solutions to problems that have been identified through the implementation of some activities that are beneficial to the development of research centers in order to have a more competitive advantage. Training activities undertaken include: customer database creation activities, creation of leaflets documentation, creation of websites / blogs, and discussion through entrepreneurship education seminars. As a form of evaluation of solutions offered activities, researchers will conduct follow-up through the method of in-depth interviews and focus group discussions involving SMEs and relevant officials as a comparison between before and after the training to the SME Specifically this study Implementing a model of industrial centers Minang craft creative motif through the adaptability of SMEs, entrepreneurship and competitive advantage that can be used by the parties involved in fostering the creative industry center.